2017
DOI: 10.1038/s41598-017-07881-7
|View full text |Cite
|
Sign up to set email alerts
|

Environmental concern-based site screening of carbon dioxide geological storage in China

Abstract: Environmental impacts and risks related to carbon dioxide (CO2) capture and storage (CCS) projects may have direct effects on the decision-making process during CCS site selection. This paper proposes a novel method of environmental optimization for CCS site selection using China’s ecological red line approach. Moreover, this paper established a GIS based spatial analysis model of environmental optimization during CCS site selection by a large database. The comprehensive data coverage of environmental elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…They concluded that the low doses of pyridine doping can trigger neutral reaction with the Brønsted acid sites and give hydrolytic stability. However, excess of pyridine could convert all of the remaining B [3] in COF-5/-10 to Lewis B [4] and cause the total and irreversible structural decomposition of the two materials. High dose of pyridine modification brings about a decrease in the gas capture performance, despite it enhances the hydrolytic stability to small extent.…”
Section: Covalent Organic Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the low doses of pyridine doping can trigger neutral reaction with the Brønsted acid sites and give hydrolytic stability. However, excess of pyridine could convert all of the remaining B [3] in COF-5/-10 to Lewis B [4] and cause the total and irreversible structural decomposition of the two materials. High dose of pyridine modification brings about a decrease in the gas capture performance, despite it enhances the hydrolytic stability to small extent.…”
Section: Covalent Organic Frameworkmentioning
confidence: 99%
“…Faced with such severe reality, the reduction of CO 2 concentration in atmosphere becomes a global concern. Carbon capture and storage (CCS) is a promising technique for significant reduction of CO 2 emission from large point sources [3,4]. CO 2 capture needs about three quarters of the total cost for the CCS system [5].…”
Section: Introductionmentioning
confidence: 99%
“…Global warming has become an increasingly serious environmental concern because of the excessive emission of carbon dioxide in human activities. [ 1–3 ] In addition to CO 2 capture technology for geological sequestration, [ 4–6 ] solar‐driven CO 2 conversion into chemical fuels is promising, which not only reduces the amount of CO 2 in the atmosphere, but also achieves carbon‐neutral cycling. [ 7–11 ] Inspired from photosynthesis in nature, the researchers have devoted themselves to the studies of photocatalytic CO 2 reduction by directly using solar energy.…”
Section: Introductionmentioning
confidence: 99%
“…This method determined a GIS-based spatial modeling of climatic variables using geostatistical techniques as GIS algorithms. The GIS algorithms were also used in the GIS tools in Iran to predict the climatic effect variability (CEV) based on several synthetic maps of the effect spatial variability of climatic variables such as that of Cai et al. (2017) .…”
Section: Introductionmentioning
confidence: 99%